BCG vaccination policy, natural boosting and pediatric brain and CNS tumor incidences - Singh, Samer; Diwakar, Amita; Singh, Rakesh K. (Frontiers in Immunology, 2023)
Bacille Calmette-Guérin (BCG) vaccination supposedly imparts and augments “trained immunity” that cross-protects against multiple unrelated pathogens and enhances general immune surveillance. Gradual reductions in tuberculosis burden over the last 3–5 decades have resulted in the withdrawal of BCG vaccination mandates from developed industrialized countries while reducing to a single neonatal shot in the rest. Concurrently, a steady increase in early childhood Brain and CNS (BCNS) tumors has occurred. Though immunological causes of pediatric BCNS cancer are suspected, the identification of a causal protective variable with intervention potential has remained elusive. An examination of the countries with contrasting vaccination policies indicates significantly lower BCNS cancer incidence in 0–4-year-olds (per hundredthousand) of countries following neonatal BCG inoculations (n=146) vs. non-BCG countries (n=33) [Mean: 1.26 vs. 2.64; Median: 0.985 vs. 2.8; IQR: 0.31–2.0 vs. 2.4–3.2; P=<0.0001 (two-tailed)]. Remarkably, natural Mycobacterium spp. reexposure likelihood is negatively correlated with BCNS cancer incidence in 0-4-year-olds of all affected countries [r(154): −0.6085, P=<0.0001]. Seemingly, neonatal BCG vaccination and natural “boosting” are associated with a 15–20-fold lower BCNS cancer incidence. In this opinion article, we attempt to synthesize existing evidence implying the immunological basis of early childhood BCNS cancer incidence and briefly indicate possible causes that could have precluded objective analysis of the existing data in the past. We draw the attention of the stakeholders to consider the comprehensive evaluation of immune training as a potential protective variable through well-designed controlled clinical trials or registry-based studies as feasible for its potential applications in reducing childhood BCNS cancer incidence.